(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Competency-based teaching (CBT) has gained prominence as an effective pedagogical approach in language education. The concept was initially introduced in the late 20th century by scholars in the field of educational psychology and pedagogy, including Benjamin Bloom and John Raven. This paper explores the impact of competency-based teaching on Russian language acquisition, analyzing its role in developing linguistic, communicative, and cultural competencies. The study also examines the advantages of this approach over traditional teaching methods and provides recommendations for its implementation in Russian language curricula. Additionally, it highlights recent research trends in the field, focusing on digital competency-based learning and personalized assessment strategies.